Resource management of mobile cloud computing networks and environments - Mastorakis, George, 1978-; Mavromoustakis, Constandinos X., 1974-; Pallis, Evangelos, 1971- (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series., 2015)
"This book reports on the latest advances in the development of computationally intensive and cloud-based applications, covering a wide range of problems, solutions, and perspectives"--